2009
DOI: 10.1007/978-3-642-00899-3_12
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Studies in Process Model Verification

Abstract: Abstract. Despite the large body of knowledge on formal analysis techniques for process models, in particular Petri nets, there has been a notable gap of empirical research into verification. In this paper we compare the few studies that report results from applying verification techniques to real-world process model collections. For this comparison we are particularly interested in the different approaches, their computational performance, and the number of errors found. Our comparison reveals that most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 51 publications
0
22
0
5
Order By: Relevance
“…Such an error is called a deadlock. It has been found that many process models in practice include such errors, and that often about 20% of the models have deadlocks or other behavioral problems [40]. Clearly, such deadlocks point to bad design.…”
Section: Business Process Models and Errorsmentioning
confidence: 99%
“…Such an error is called a deadlock. It has been found that many process models in practice include such errors, and that often about 20% of the models have deadlocks or other behavioral problems [40]. Clearly, such deadlocks point to bad design.…”
Section: Business Process Models and Errorsmentioning
confidence: 99%
“…Maintenance and quality assurance of these process models is a critical challenge given this big number of models and modelers. Indeed, different quality issues have been observed: up to 20% of all models in collections from practice contain errors [2], and many casual modelers are not sufficiently trained [3].…”
Section: Introductionmentioning
confidence: 99%
“…In practice a considerable percentage of process models has quality issues, with often 5% to 30% of the models having problems with soundness [9]. The reason for at least some of these issues is the growth of many process modeling initiatives.…”
Section: Introductionmentioning
confidence: 99%